GANAB and PKD1 Variations in a 12 Years Old Female Patient With Early Onset of Autosomal Dominant Polycystic Kidney Disease - Waldrop, Elizabeth; Al-Obaide, Mohammed A. I.; Vasylyeva, Tetyana L. (Frontiers in Genetics, 2019)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) typically results from a mutation in the PKD1 and PKD2 genes, which code for polycystin-1 (PC1) and polycystin-2 (PC2) respectively. Mutations in these genes promote renal cystic dysplasia and are a significant cause of End-Stage Kidney Disease (ESKD). Polycystic kidney disease-3 (PKD3), another form of ADPKD, is caused by mutations in glucosidase II alpha subunit (GANAB) gene and present in mid- and late adulthood. We report a description of an ADPKD case in a 12-year-old female presented bilateral renal cysts in adolescence. Two mutations in two genes PKD1 and GANAB were identified by targeted capture and next-generation sequencing (NGS) on an Illumina sequencing system. The identified PKD1 mutation p.Pro61Leu: c.182C>T (CCC˃CTC) a missense type of uncertain clinical significance. However, the identified PKD1 mutation can alter transcription factors motifs and consequently disturb the transcription process. The second mutation identified in GANAB locus, p.Arg61Ter: c.181C>T, a nonsense type, CGA˃TGA. The mutation is unreported pathogenic variant can cause loss of the glucosidase II alpha subunit normal protein function. Both the patient father and paternal grandmother had a history of ADPKD but never were tested. This case is the first case of combine presentation on PKD1 and PKD3 in a pediatric patient with nephrolithiasis.